Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1243
|View full text |Cite
|
Sign up to set email alerts
|

Driving Performance while Engaged in MP-3 Player Interaction: Effects of Practice and Task Difficulty on PRT and Eye Movements

Abstract: Summary:The purpose of this study was to examine the effects of iPod interactions on driver performance over several sessions to determine the distraction effect of iPods on driver performance, as well as to see if performance decrements declined with practice. Nineteen younger drivers (mean age = 19.4, range 18 to 22) participated in a seven-session study in the University of Calgary Driving Simulator. Drivers encountered a number of critical events such as pedestrian incursions, lead vehicle braking, and pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…The complexity factors were kept constant across the conditions. Even though we did not utilize alphabetically ordered menus in order to avoid unwanted learning effects, the iPod study of Chisholm, Caird, Lockhart, Fern, and Teteris [1] seems to indicate that the search will be demanding even with this feature enabled if there is enough search items in the menu. A major shortcoming in our experimental design was the absence of object detection or reaction task measures.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity factors were kept constant across the conditions. Even though we did not utilize alphabetically ordered menus in order to avoid unwanted learning effects, the iPod study of Chisholm, Caird, Lockhart, Fern, and Teteris [1] seems to indicate that the search will be demanding even with this feature enabled if there is enough search items in the menu. A major shortcoming in our experimental design was the absence of object detection or reaction task measures.…”
Section: Discussionmentioning
confidence: 99%
“…The search tasks simulated a situation in which the participant searches for a certain song in an in-car music player. The distraction effects of searching music tracks while driving are some of the most studied topics in distraction research (e.g., Jeon et al, 2015;Lee et al, 2012;Chisholm et al, 2007;Salvucci et al, 2007). The song titles were artificial and were generated with an online song name generator (http://www.songname.net/).…”
Section: Environment and Toolsmentioning
confidence: 99%
“…In a simulator experiment, Chisholm et al [10] looked at manual-visual interactions with mp3 players while driving. They found that complicated interactions with the mp3 player increased reaction time to road hazards.…”
Section: Related Researchmentioning
confidence: 99%